Association of the longitudinal trajectory of urinary albumin/creatinine ratio in diabetic patients with adverse cardiac event risk: a retrospective cohort study - Li, Hui; Ren, Yajuan; Duan, Yongguang; Li, Peng; Bian, Yunfei (Frontiers in Endocrinology, 2024)
Objective Baseline urinary albumin creatinine ratio (uACR) is proved to be significantly associated with major adverse cardiac events (MACEs) risk. However, data on the association between longitudinal trajectory patterns of uACR, changes of glycated hemoglobin A1c (HbA1c) and subsequent MACEs risk in diabetic patients are sparse. Methods This was a retrospective cohort study, which included 601 type 2 diabetes mellitus (T2DM) patients (uACR< 300 mg/g) admitted to First Hospital of Shanxi Medical University and Second Hospital of Shanxi Medical University from January 2015 to December 2018. uACR index was calculated as the urinary albumin (mg)/creatinine (g), and latent mixed modelling was used to identify the longitudinal trajectory of uACR during the exposure period. The deadline of follow-up was December 31, 2021. The primary outcome was the MACEs. Results Four distinct uACR trajectory were identified, including the low-stable group (uACR 5.2-38.3 mg/g, n=112), moderate-stable group (uACR 40.4-78.6 mg/g, n=229), high-stable group (uACR 86.1-153.7 mg/g, n=178) and elevated-increasing group (uACR 54.8-289.4 mg/g, n=82). Relative to the low-stable uACR group, patients in the high-stable and elevated-increasing uACR group were more likely to be old people, current smokers, and had long DM course, higher levels of 2h PG, HbA1c, NT-proBNP, uACR and LVMI, while featured with the higher prevalence of hypertension and lower proportion of β-receptor blocker treatment (P<0.05). During a median follow-up of 45 (24-57) months, 118 cases (19.6%) of MACEs were identified. The Kaplan-Meier survival curve showed that compared with the low-stable uACR group, the MACEs incidences were significantly increased in the high-stable (HR=1.337, 95% CI: 1.083 to 1.652, P=0.007) and the elevated-increasing (HR=1.648, 95% CI: 1.139 to 2.387, P=0.009) uACR groups. Multivariate Cox proportional hazard models indicated that, after adjusting for potential confounders, the HR for MACEs risk were 1.145 (P=0.132), 1.337 (P=0.007) and 1.648 (P=0.009) in the mediate-stable, high-stable and elevated-increasing uACR groups, respectively. The ROC curve showed that after adding uACR, HbA1c, or both, the AUC were 0.773, 0.792 and 0.826, which all signified statistically significant improvements (P=0.021, 0.035, 0.019, respectively). Conclusions A long-term elevated increasing uACR is associated with a significantly increased risk of MACEs in diabetic patients.